2016
DOI: 10.3233/jad-150910
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study

Abstract: Background Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. Objective To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. Methods The data came from the Keys to Optimal Cognitive Aging (KOCOA) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
(52 reference statements)
4
14
1
Order By: Relevance
“…We cannot explain this finding, which contrasts the general scientific opinion promoting that the content of omega-3 PUFA in the human brain generally increases with age over the first 2 decades and then levels off [41] or even drops [3,12]. However, previous research on cardiovascular patients has shown that a higher omega-3 index was associated with longer survival [42].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We cannot explain this finding, which contrasts the general scientific opinion promoting that the content of omega-3 PUFA in the human brain generally increases with age over the first 2 decades and then levels off [41] or even drops [3,12]. However, previous research on cardiovascular patients has shown that a higher omega-3 index was associated with longer survival [42].…”
Section: Discussioncontrasting
confidence: 52%
“…In a cross-sectional study in dementia-free Framingham study participants (n = 1,575, mean age: 67 years, SD ±9), low levels of EPA and DHA in erythrocytes were associated with small brain volumes and a vascular pattern of cognitive impairment [11]. Another cross-sectional study from Japan including 158 non-demented participants (mean age: 84.1 years, SD ±3.4) showed that higher global cognitive function was significantly associated with higher levels of serum EPA and DHA+EPA after controlling for confounders [12]. Nonetheless, there is conflicting evidence from population-based studies of the relationship between blood (plasma or erythrocyte) omega-3 PUFA composition and some form of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell membrane fluidity also influences the processing of APP and cellular phagocytosis, both of which might affect Aβ generation and clearance. A high dietary intake of polyunsaturated fatty acids such as docosahexaenoic acid, which maintain membrane fluidity, have a beneficial effect on cognition in patients with AD 91,92 . The study of membrane fluidity in AD might provide insights into the alteration of membrane-dependent biological functions related to Aβ, such as phagocytosis, endocytosis, macropinocytosis and autophagy.…”
mentioning
confidence: 99%
“…In the cross-sectional study using the data from the Keys to Optimal Cognitive Aging (KOCOA) study, an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan, higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia [15]. In the retrospective cohort study, an association between red blood cell (RBC) DHA + EPA levels and age-associated cognitive decline was not observed in a cohort of older, dementia-free women [16].…”
Section: The Observational Studies Which Investigated the Associationmentioning
confidence: 99%